Evaluation of pathogenicity level of three different strains of fusarium oxysporum in Musa acuminata cv. Berangan - Munusamy, Umaiyal; Mohd-Yusuf, Yusmin; Zaidi, Kamilatulhusna; Baharum, Nadiya Akmal; Othman, Rofina Yasmin (World Research Association, 2019)
Fusarium oxysporum is one of the most adaptive and pathogenic fungus that causes wilting in banana. It is regarded as one of the economically destructive fungus and control of this disease is always ineffective once the disease becomes established in banana plantations. Various researches have been carried out, but sustainable solution is yet to achieve. In this study, we identified the infection phenotypically through LSI and RDI which can be only done after 5 th -week of post inoculation. With qPCR application, we identified the infection level much faster within 2 to 96 hrs. Disease severity index obtained from LSI and RDI value showed that Berangan is highly susceptible towards C1 HIR, 9888 and 2296. Meanwhile, qPCR analysis besides showing infection pattern as early as 2 hrs in Berangan was infected with C1 HIR, 9888 and 2296. We also found that additional information such as specific genes were expressed in the Berangan infected with C1 HIR, 9888 or 2296. This information can be used to identify the fusarium strain that is actually infecting Berangan. This could help planters to identify early infection of fusarium as well as strain recognition. © 2019, World Research Association. All rights reserved.